Correlation among monitoring methods of surface cleaning and disinfection in outpatient facilities - Furlan, Mara Cristina Ribeiro (2019)
Objectives: To evaluate the correlation among microbiological culture, ATP bioluminescence assay, and visual inspection in monitoring the effectiveness of surface cleaning and disinfection in an outpatient facility and determine the ATP bioluminescence cutoff capable of indicating a clean surface regarding microbiological evaluation. Methods: Exploratory, cross-sectional, and correlation study consisting of 720 evaluations in five surfaces before and after cleaning and disinfection. The results were used to run two-proportions tests, calculate Spearman's correlation, and plot the receiver operating characteristic curve. Results: Similar proportions (p≥0.05) occurred for non-approval rates between ATP-bioluminescence and aerobic colony count only when the evaluations of all the surfaces before and after cleaning and disinfection were put together. There was a significant correlation between the ATP quantification and microbial count methods for the reception desk and the stretcher. Receiver operating characteristic analysis indicated that ATP quantification showed a significant result in comparison with aerobic colony count (p=0.044). Conclusion: There was a discrete correlation between the ATP quantification and microbial count methods for two surfaces. It is suggested that surfaces showing values ≤49 relative light units are clean.